Exploration and application of in-situ stress estimation method based on core disking phenomenon of boreholes - YAN Shaokun; WANG Chenghu; GAO Guiyun; LIU Jikun; DAI Xiangqian (Dizhi lixue xuebao)
Objective  Rock core disking is a typical phenomenon that occurs in environments with high in-situ stress. The geometric characteristics and section shape of rock disking are related to the state of in-situ stress, and the site where this phenomenon occurs may be unsuitable for measuring in-situ stress. To obtain more comprehensive in-situ stress data from a wider range of sources, according to this phenomenon, in-situ stress estimation is conducted based on the internal relationship between the in-situ measurement data and the original in-situ stress, and the obtained result can supplement the in-situ stress measurement data.   Methods  According to the relevant hypotheses and theories worldwide, the change in core section stress and core internal energy during the core disking phenomenon was analyzed. The physical and geometric characteristics of the disked rock cores were measured, combined with the stress state of the original rock, and an in-situ stress estimation formula based on core disking characteristics was constructed. The results were compared with those of the other formulas.   Results  The geometric characteristics of 73 representative rock disks in the 30–120 m depth section of the Dalianshan borehole in Dandong, Liaoning Province, where the phenomenon of rock core disking occurs, are measured, and the physical properties of the core are tested. The value of the in-situ stress in this section is estimated using the established in-situ stress estimation formula to supplement and perfect the measured hydraulic fracturing data and better reveal the law of in-situ stress variation.   Conclusion  This section is estimated according to other in-situ stress estimation formulas based on the phenomenon of core disking proposed by scholars worldwide; the calculated results either deviate from reality or are dispersed in the distribution. Compared with these formulas, the in-situ stress data estimated by this formula are more in line with reality and meet the stress conditions for the generation of core disking.   Significance   The results show that the results obtained using this method can complement and perfect the in-situ stress data of the core disking depth section.